Shen Wei Dance Arts 2004 Review - Sansom, Bruce (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Shen Wei, The Rite of Spring, China, Folding.
Dentro del apartado "Dance Now. 2004 Reviews".